Cost-Effectiveness of Open vs. Endoscopic Repair of Zenker's Diverticulum. (May 2022) - Lee, Paul B.; Hojjat, Houmehr; Lucas, Jordyn; Chung, Michael T.; Spillinger, Aviv; Meleca, Joseph B.; Svider, Peter; Shkoukani, Mahdi; Johnson, Andrew; Folbe, Adam
Objective: To evaluate the cost-effectiveness of open versus endoscopic surgical repair of Zenker's diverticulum. Methods: In this study, an economic decision tree was utilized to compare the cost-effectiveness of open surgery compared to endoscopic surgery. The primary outcome in this analysis was the incremental cost-effectiveness ratio (ICER) that was calculated based on the economic decision tree. The probability of post-operative esophageal perforation complications, revision rates, and effectiveness of each procedure along with associated costs were extracted to construct the decision tree. Univariate sensitivity analysis was then utilized to determine how changes in esophageal perforation rate affect the cost-effectiveness of each surgical approach. Results: The ICER of open surgery for Zenker's diverticulum was 67 877, above most acceptable willingness to pay (WTP) thresholds. Additionally, if the probability of esophageal perforation with endoscopic surgery is above 5%, then open surgery becomes a more cost-effective option. Probabilistic sensitivity analysis using Monte Carlo simulations also showed that at the WTP thresholds of 30 000 and 50 000, endoscopic surgery is the most cost-effective method with 83.9% and 67.6% certainty, respectively. Conclusion: Open surgery and endoscopic surgery are 2 treatment strategies for Zenker's diverticulum that each have their own advantages and disadvantages that can complicate the decision-making process. With no previous cost-effectiveness analysis of open versus endoscopic surgery for Zenker's diverticulum, our results support the endoscopic approach at most common WTP thresholds. Particularly with the current focus on rising healthcare costs, our results can serve as an important adjunct to medical decision-making for patients undergoing treatment for Zenker's diverticulum.